2018
DOI: 10.1017/s1368980017003901
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of vitamin D deficiency in the older Polish population: results from the PolSenior study

Abstract: Vitamin D deficiency/insufficiency is frequent in the older Polish population and associated with functional disability and impaired mobility of seniors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…This study found that there was a significant difference of education level between vitamin D deficiency group and insufficient-normal group. Lower educational level has been associated with vitamin D deficiency in Saudi Arabia and Poland [28, 29]. Similar observation was found in this study since more than half of the participants (116 women, 56.86%) had education level of middle school or lower.…”
Section: Discussionsupporting
confidence: 88%
“…This study found that there was a significant difference of education level between vitamin D deficiency group and insufficient-normal group. Lower educational level has been associated with vitamin D deficiency in Saudi Arabia and Poland [28, 29]. Similar observation was found in this study since more than half of the participants (116 women, 56.86%) had education level of middle school or lower.…”
Section: Discussionsupporting
confidence: 88%
“…In line with the present study, there are reports in the literature mentioning that the serum 25-OH Vitamin D levels vary considerably among seasons, peak 30-60 days following the exposure to sunlight in summer months and drop to the lowest level toward the end of winter months (1,20). In a study by Wyskida et al, sufficient vitamin levels were most frequent in August in both men and women, while the lowest values were observed in women in January and in men in March (21). Results of the present study are similar to the results of the study by Gonzalez Molero et al, conducted in Spain to examine seasonal variations in the 25-OH Vitamin D levels (9).…”
Section: Discussionsupporting
confidence: 46%
“…The group consisted of 480 subjects drawn from a population-based community dwelling cohort of older subjects (PolSenior study [12]) without a history of cancer, matched according to sex, age (73 ± 6 years), occurrence of diabetes (34.8%), and hypertension (81.4%).…”
Section: Methodsmentioning
confidence: 99%